CD8+T Cell Exhaustion and Immune Checkpoint Blockade Treatment - Song, Jiani; Yuan, Quan; Zhou, Yuxin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
T cells play an important role in anti-tumor immunity. Its subset that contains the surface receptor CD8, also called cytotoxic T cells, functions to facilitate tumor cell elimination. Chronic exposure of CD8+ T cells to antigens and inflammation can cause the T cells to lose their functions as well as changes in their surface expressions, named T cell exhaustion (Tex). This article reviews the molecular mechanisms of this cellular process and the influence of the tumor microenvironment (TME) on it. This article focuses on the mechanism of action of the four major upregulated immune checkpoint proteins (ICPs) and introduces ICB therapies targeting each ICP. Based on these mechanisms, scientists have suggested various interventions to reverse T-cell exhaustion. Recent clinical data show that although ICB therapy has significant efficacy in some patients, its limitations in patient selection limit the popularization of the treatment effect. ICB which curbs Tex by blocking the signal pathways that suppress T cell functions, summarizes the current understandings and progress, and identifies the gaps on this topic.